Acute sleep hygiene strategy improves objective sleep latency following a late-evening soccer-specific training session: A randomized controlled trial - Vitale, J. A.; La Torre, A.; Banfi, G.; Bonato, M. (Journal of Sports Sciences, 2019)
The aim of this study was to evaluate the effects of sleep hygiene (SH) education on sleep quality in soccer players after a late-evening small-sided-game (SSG) training session. Twenty-nine non-professional players were recruited and allocated to either an experimental group (EG, n = 17) that received SH education, or a control group (CG, n = 12). SSG consisted of 3 × 4 min in a 4vs4, with 3 min of recovery and was performed at 8.00 p.m. Sleep quality was monitored via actigraphy and sleep diary entries before (PRE) and two nights after (POST1, POST2) the SSG. Sleep latency (SL) differed between the two groups at POST1 (4.9 ± 5.4 vs. 15.5 ± 16.1 for EG and CG, respectively; p = 0.017, effect size [ES] = 2.0); SL values were lower at POST1 compared to PRE for the EG (-47%; p = 0.021, ES = 0.6). Subjective sleep quality was better in the EG than the CG at POST1 (8.6 ± 1.0 vs. 7.1 ± 2.0 for EG and CG, respectively; p = 0.016, ES = 0.9) with a significant improvement over PRE-values (+11.0%, p = 0.004, ES = 0.8). Although SL and subjective sleep quality did not decrease significantly from POST1 to POST2 values at POST2 no longer differed significantly form baseline and, hence, indicate that observed effects may be short-lasting. No other objective sleep indices were influenced by late-evening training or SH practices implemented by the EG. Soccer players may benefit from acute SH strategies to reduce the time to sleep onset after late-evening training sessions.